Correction: Chitin-acetate/DMSO as a supramolecular green CO2-phile. Issue 34 (18th March 2016) - Eftaiha, Ala'a F.; Alsoubani, Fatima; Assaf, Khaleel I.; Nau, Werner M.; Troll, Carsten; Qaroush, Abdussalam K.
Abstract : Correction for 'Chitin-acetate/DMSO as a supramolecular green CO2 -phile' by Ala'a F. Eftaiha et al., RSC Adv., 2016, 6, 22090–22093.